Independence Day for the Services Directive: Visser - Jukka Snell (Kluwer Law International, 2022)
As so often in EU law, the significance of changes to the Treaties or legislation only emerges gradually as a result of the case law of the Court. As the most obvious example, the impact of the provisions on EU citizenship that were introduced in Maastricht only became clear once the Court handed down rulings in cases such as Martínez Sala and Baumbast. Something similar may now be taking place for the Services Directive. After a slow start, the Court is increasingly being given the chance to rule on the meaning of the obscure political compromises that the Directive contains. The Visser judgment is undoubtedly a key step in this process. The Grand Chamber of the Court was faced with a number of classic questions of free movement law, but in the context of the application of the Services Directive rather than the Treaty freedoms. The answers the Court provided serve to establish the autonomous significance of the Directive as a liberalizing instrument. It is not just a minor restatement of the Treaty rights, but is independent of them, and goes beyond them.